2011
DOI: 10.2147/ijn.s22731
|View full text |Cite|
|
Sign up to set email alerts
|

Thiolated chitosan nanoparticles as a delivery system for antisense therapy: evaluation against EGFR in T47D breast cancer cells

Abstract: Thiolated chitosan has high transfection and mucoadhesive properties. We investigated the potential of two recently synthesized polymers: NAC-C (N-acetyl cysteine-chitosan) and NAP-C (N-acetyl penicillamine-chitosan) in anticancer drug delivery targeting epidermal growth factor receptor (EGFR). Doxorubicin (DOX) and antisense oligonucleotide (ASOND)-loaded polymer nanoparticles were prepared in water by a gelation process. Particle characterization, drug loading, and drug release were evaluated. To verify drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Thus, CTS-based NPs were formulated via gelation with sodium sulfate as nanocarriers for doxorubicin (DOX) and antisense oligonucleotide (ASOND). They displayed a spherical, uniform shape with a mean particle size of 150-300 nm [114]. Another option for CTS-based particles is ionic gelation with TPP, feasible for both CTS and thiolated CTS-GSH [29].…”
Section: Nanostructures From Chitosan and Hyaluronic Acid-based Thiomersmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, CTS-based NPs were formulated via gelation with sodium sulfate as nanocarriers for doxorubicin (DOX) and antisense oligonucleotide (ASOND). They displayed a spherical, uniform shape with a mean particle size of 150-300 nm [114]. Another option for CTS-based particles is ionic gelation with TPP, feasible for both CTS and thiolated CTS-GSH [29].…”
Section: Nanostructures From Chitosan and Hyaluronic Acid-based Thiomersmentioning
confidence: 99%
“…Results showed that the corneal status significantly improved in more than 60% of patients, with most of them starting to show beneficial results as early as 10 min after a single instillation of CTS-NAC [162]. This polymer has also been tested, along with CTS-NAP (CTS-N-acetylpenicillamine), as a platform to deliver doxorubicin (DOX) and antisense oligonucleotides (ASOND) targeting EGFR, which is a transmembrane receptor overexpressed in most of the cases of breast cancer with poor prognosis [114]. When evaluated on T47D cells (human breast epithelial tumor cells), these NPs showed similar properties as the ones stated before, such as sustained release, good encapsulation efficiency, and stability (especially those carrying ASOND), so the clinical potential of this formulation is obvious.…”
Section: Thiomer-based Conjugates For Taxanes and Other Anticancer Api Administrationmentioning
confidence: 99%
“…For the analysis of the amount of immobilized −SH groups of these thiolated chitosans, Ellman’s reagent optionally with previous reduction of disulfide bonds with borohydride or iodometric titration can be used . Phadungcharoen et al, for instance, have conducted the Ellman’s assay via smartphone, providing an easy, fast, and reliable analysis of thiolated polymers without access to sophisticated equipment. …”
Section: Chitosan: Its Chemistry and Thiolationmentioning
confidence: 99%
“…Moreover, 5-aminolevulinic acid-incorporated nanoparticles of methoxy poly(ethylene glycol)-chitosan copolymer are used in photodynamic therapy [ 191 ], while, FVIII-chitosan nanoparticles [ 192 ], cyclosporin A-loaded, PEGylated chitosan-modified, lipid-based nanoparticles [ 193 , 194 ], and chitosan and poly(lactic- co -glycolic acid) incorporated nanoparticles (heparin) are also prepared for quick CNS therapeutics [ 195 ]. Similarly, thiolated chitosan nanoparticles are also prepared for drug delivery system for antisense therapy [ 196 ] ( Table 2 ).…”
Section: Drug Delivery Methodsmentioning
confidence: 99%